PECULIARITIES OF SILICOTUBERCULOSIS IN THE WORKERS OF FERROUS METALLURGY ENTERPRISES - V. V. Zakharenkov; O. A. Morozova; I. V. Viblaya (Acta Biomedica Scientifica, 2012)
The results of long-term dispensary supervision (14 years) of 284 silicosis patients (including 54 silicotuberculosis patients) worked at Kuznetsk Metallurgical Plant have shown that high concentration of dust in air with 5% content of free silicon dioxide promotes the development of non-complicated silicosis as well as silicotuberculosis. This dispensary supervision, has been conducted by the physicians of scientific and consultative department of FSBI "RI CPHOD" SB RAMS in Novokuznetsk. Fast development of silicosis is risk factor for silicotuberculosis (р < 0,05). Slow development of silicosis is much rarely associated by tuberculosis infection. The patients with non-complicated. silicosis and. silicotuberculosis have the signs of pneumonia (oftener in non-complicated silicosis) and. chronic obstructive pulmonary disease (oftener in silicotuberculosis) according to the results of chest radiography.